A 6-y retrospective cohort study of family satisfaction with critical care and decision-making in an Australian intensive care unit. Issue 3 (May 2022) - Khan, Shahrukh; Digby, Robin; Giordano, Nicholas A.; Hade, Sharon; Bucknall, Tracey K.
Abstract: Background: Partnering with patients and families to make decisions about care needs is a safety and quality standard in Australian health services that is often not assessed systematically. Objective: The objective of this study was to retrospectively evaluate satisfaction with care and involvement in decision-making among family members of patients admitted to the intensive care unit (ICU). Methods: A retrospective cohort analysis of a satisfaction survey administered to family members of patients admitted to an ICU in an Australian metropolitan tertiary care hospital from 2014 to 2019 was conducted. The Family Satisfaction in the Intensive Care Unit questionnaire (FSICU) questionnaire was used to assess overall satisfaction, satisfaction with care, and satisfaction with decision-making on a scale from "poor" (0) to "excellent" (100). Results: In total, 1322 family members fully completed the survey. Respondents were typically direct relatives of ICU patients (94.2%) with an average age of 52.6 years. Most patients had an ICU length of stay <7 d (56.8%), with most patients being discharged to the ward (96.8%). The overall mean satisfaction score was high among respondents (90.26%). Similarly, mean satisfaction with care (93.06%) and decision-making (89.71%) scores were high. Satisfaction with decision-making scores remained lower than satisfaction with care scores. Multivariable modeling indicated that those younger than 50 years reported higher satisfaction scores (p = 0.006) and those with prolonged lengths of stay in the ICU were associated with lower overall satisfaction scores (p = 0.039). Despite some criticism of waiting times and noise levels, responses showed sincere gratitude for patients' treatment in the ICU and appreciation for the care, skill, and professionalism of the staff. Conclusion: Very high satisfaction levels were reported by family members during this study. Routine, prospective evaluations of family member satisfaction with ICU experiences are feasible and can be leveraged to provide insight for clinicians and administrators seeking to improve family satisfaction with decision-making and care in ICU settings and meet national standards.